State ownership, information asymmetry and cash holding: Impact of COVID-19 on Chinese-listed firms - Yu, Danni; Soh, Weini; Noordin, Bany Ariffi Amin; Yahya, Mohamed Hisham; Latif, Badar (Frontiers in Psychology, 2022)
This study investigates the relationship between information asymmetry and cash holdings under the impact of the coronavirus disease 2019 (COVID-19) in China. It likewise explores how state ownership dominates their nexus, particularly during the pandemic. COVID-19 caused increases in cash holdings, and that the information asymmetry’s effect on cash holdings is more pronounced over the COVID-19 period. Additionally, information asymmetry has a weaker effect on corporate cash holdings for state-owned enterprises (SOEs) under the pandemic. Overall, the study shows that state ownership moderates information asymmetry’s impact on cash holdings and softens firms’ precautionary motive for cash holdings during the pandemic.